A Quantitative Analysis of SIMKES User Satisfaction in Outpatient Units Using the EUCS Approach - Adnan Syarif Mustaqim; Wahyu Wijaya Widiyanto (International Journal of Public Health, 2025)
The implementation of health information systems such as SIMKES (Sistem Informasi Manajemen Kesehatan) plays a crucial role in enhancing administrative efficiency and service delivery in primary healthcare centers. However, user satisfaction remains a key indicator of system effectiveness, especially in outpatient service units. This study aims to evaluate the satisfaction level of health personnel toward the implementation of SIMKES at the outpatient unit of Teguhan Health Center, Ngawi, Indonesia. Employing a descriptive quantitative method, this research involved a census of 17 respondents using a validated questionnaire based on the End-User Computing Satisfaction (EUCS) model, which comprises five dimensions: content, accuracy, format, ease of use, and timeliness. The data were analyzed using frequency distribution and mean scoring to categorize satisfaction levels. Results showed that the overall satisfaction score was 73.58, indicating that users were generally satisfied with the system. All five EUCS dimensions were categorized as satisfactory, with the highest rating in the format dimension and the lowest in timeliness. Despite the overall positive assessment, users reported issues related to system speed, technical bugs, and limited guidance for system navigation. The findings suggest that while SIMKES supports outpatient service delivery effectively, improvements are needed in system responsiveness and user support to enhance satisfaction and usability. This study contributes to the ongoing evaluation and development of health information systems in resource-limited primary care settings.